A Foucauldian-Vygotskian Analysis of the Pedagogy of Academic Integrity - Crook, Stephanie (Discourse and Writing/Rédactologie, 2019)
This paper provides a Foucauldian-Vygotskian analysis of the pedagogy of academic integrity in the North American post-secondary context. In particular, the issue of ‘unintentional plagiarism’ is examined. The main implication of this analysis is that the notion of unintentional plagiarism places students, particularly junior students, in a position of being asked to engage with complicated academic discourses in the absence of any internalized sense of academic integrity. This occurs because the removal of intent from the concept of academic integrity undermines its meaning, and this leads students to believe that they do not have access to the monitoring processes that they need in order to ensure that their work is properly cited. Several suggestions for improving the pedagogy of academic integrity emerge from this analysis and these are outlined in the paper.